Big Data and Performance: What Can Management Research Tell us?. (8th May 2019) - Sena, Vania; Bhaumik, Sumon; Sengupta, Abhijit; Demirbag, Mehmet
Abstract: The special issue focuses on the theory and evidence linking the use of Big Data related technologies by businesses with their performance. Here we connect the papers accepted for the special issue to the overarching theme of Big Data as an emerging concept within the business management literature. We present two prominent case studies examining the use Big Data technologies on performance and strategy, followed by a discussion on how themes around Big Data and Performance may be examined from a theoretical perspective. Finally, based on a synthesis of papers in the current issue, we discuss the emerging issues and trends within the academic literature, relevant for future research.